Parents' Strategy in Using Gadgets as a Source of Character Education - Yulianti, Dedek; Montessori, Maria; Ananda, Azwar; Rahmi, Tuti (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to analyze gadgets and identify strategies and obstacles parents face in using gadgets as a source of character education for children aged 10-12 years in the Kerasaan I area. This research is qualitative research with a case study approach. They are implemented in the Kerasaan I village, Simalungun Regency, North Sumatra. Observation, interviews, and documentation carried out data collection techniques, while data analysis was done by data reduction, data presentation, and drawing conclusions and then verified. The results of this study are gadgets for children aged ten years and 12 years used for the need to find and add information in completing assignments given by the teacher. This can create a sense of responsibility for children. Meanwhile, children aged 11 years tend to use gadgets to play online games. If they continue, it can cause addiction in children. So the parent's strategy in guiding children to use gadgets is to limit time, give directions, give advice, and provide supervision. As for the obstacles, parents feel when they want to guide their children to use gadgets, children prefer to be silent, and children show uncontrolled emotions when parents want to know what children access through their gadgets. In conclusion, gadgets are used by children in the Kerasaan I area as a learning resource which in turn becomes a form of responsibility towards children